Sarcoidosis-associated acro-osteolysis. Issue 3 (2nd March 2021) - Patel, Vishal; Case, Robert; Kalra, Saminder; Patel, Divya
Abstract : Sarcoidosis is characterised by the formation of noncaseating granulomas classically affecting lungs, lymph nodes and skin. Osteoarticular involvement affects up to 15% of patients; however, acro-osteolysis, destruction involving distal phalanges of fingers and toes, associated with sarcoidosis, is extremely rare. A 44-year-old woman with a history of biopsy-proven sarcoidosis managed with prednisone and methotrexate presented with swelling and pain in the distal fingers of her right hand without skin manifestations. Radiographic imaging showed erosion of distal phalanges on second, third and fifth fingers and bone resorption in bilateral toes. A biopsy of the finger lesions showed noncaseating granulomas consistent with sarcoidosis. She was diagnosed with sarcoid acro-osteolysis and started on adalimumab with clinical and radiographic improvement. While most cases of osteoarticular sarcoidosis are asymptomatic and respond to standard immunosuppression, we present a case with progressive and refractory clinical course. This is the first reported case of sarcoid acro-osteolysis affecting the toes.